Interplay between wear and thermal expansion in 6082 aluminum: a simulation and experimental study - Tian, Yang; Kalifa, Mohamed; Khan, Muhammad; Yang, Yifan (MDPI, 2024)
This study investigates how wear and thermal expansion interact in 6082 aluminum, utilizing a pin-on-disc tribometer and finite element analysis under diverse mechanical conditions. The findings show that thermal expansion reduces contact area by forming a protrusion at the contact interface. This interaction between wear and thermal expansion causes dynamic shifts in the contact region and pressure distribution, affecting the disc center and altering wear progression and temperature patterns. High thermal expansion shifts maximum wear from the contact center to outer regions, especially at higher speeds and loads. Without thermal expansion, wear-only conditions overestimate friction dissipation, resulting in a higher peak temperature. These results highlight the critical role of thermal expansion in shaping wear patterns and contact behavior in sliding applications. This research offers insights for optimizing tribological performance in 6082 aluminum, with potential applications in other materials.
Keywords: 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; wear; finite element analysis; pin-on-disc tribometer; thermal expansion